Comparison of Vector Tasks in Indonesian and Singaporean Mathematics Textbooks - Theodore Dwivaland Fophin; Nurjanah; Didi Suryadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Vector is one of the most important subjects in mathematics, but many students face difficulties in learning vector. To find out the cause, this study is conducted to find the differences and similarities in learning opportunities presented in the vector tasks from Indonesian and Singaporean mathematics textbooks. Therefore, vector tasks from the two books are compared with the aspects of representations, contextuality, and response types. Firstly, this study finds out that the chosen Indonesian textbook provides fewer learning opportunities than the chosen Singaporean textbook in terms of vector tasks. Secondly, this study also finds out that the Indonesian textbook tends to present tasks in visual representation, while the Singaporean textbook tends to present tasks in pure mathematics form. Thirdly, this study also finds out that Indonesian textbook usually uses applicative tasks that correlate with real-life situations, while the Singaporean textbook does the otherwise. Lastly, this study also finds out that both textbooks mostly use close-ended tasks.